Wheeze in preschool children and its relation with doctor diagnosed asthma. - Luyt, D K (1994)
OBJECTIVE--To describe the characteristics of wheeze and its relation with doctor diagnosed asthma in children aged 5 years and under. DESIGN--Questionnaire survey of population based random sample of children registered on Leicestershire Health Authority's child health index for immunisation; questionnaire completed by parents. SUBJECTS--1650 white children born in 1985 to 1989 who were surveyed in 1990. MAIN OUTCOME MEASURES--Age distribution, severity, precipitants, seasonal characteristics, and diurnal variation of wheeze, family history of asthma/atopy, and their association(s) with doctor diagnosed asthma. RESULTS--There were 1422 replies (86.2%). Two hundred and twenty two (15.6%) were reported to have wheezed and of these 121 (8.6%) had formally been diagnosed as having asthma. More than 80% of the former had recurrences of wheeze and 40% (72) had three or more episodes in the preceding 12 months. Age, number of episodes per year, the severity of shortness of breath with attacks, and precipitants other than colds were the major factors determining the probability that a wheezy child will be diagnosed as having asthma. The data also suggest that despite the strong association of symptom based criteria with the label asthma, asthma was not diagnosed by these same severity criteria in one quarter of cases. CONCLUSIONS--Clinical and physiological follow up studies of children identified as asthmatic by the above criteria during the preschool years should validate or refute the predictive value of these measures of wheeze severity.